The Utilization of Drones with Bird Eye View Techniques in the 'Anthropogenic Sea' Documentary Film to Improve the Quality of Visual Narrative and Spatial Perception of the Audience - Rizky Rahman Baihaqi; Iwan Koswara; Priyo Subekti (Journal Research of Social Science, Economics, and Management, 2025)
This study tested the effectiveness of the Bird's Eye View (BEV) technique in documentaries themed on anthropogenic marine environmental damage to improve the quality of visual narrative and audience spatial perception. Using a mixed methods approach with a quasi-experimental design (Posttest-Only Control Group Design), 40 students of Universitas Padjadjaran participated, divided into an experimental group (watching a movie with BEV) and a control group (without BEV). Data collection was carried out through a Likert scale questionnaire and interviews, then analyzed using the Mann-Whitney U test. Results showed significant differences (p=0.014 < 0.05) between the two groups, where the experimental group showed better quality of visual narrative and spatial perception. These findings confirm the effectiveness of BEV techniques in communicating the scale and complexity of environmental issues visually and spatially. This research contributes to the development of documentary film narratives and environmental communication literature, with practical implications for filmmakers to utilize BEVs to enhance the visual impact and spatial perception of audiences in environmental education.